Ruminative Thinking among Military Personnel of the Armed Forces of Ukraine - Avhustiuk , Mariia; Pasichnyk , Ihor; Balashov , Eduard; Kalamazh , Ruslana (Insight: the psychological dimensions of society, 2025)
The present study aims to examine the characteristics of ruminative thinking among military personnel of the Armed Forces of Ukraine. Methods. A total of 297 military personnel voluntarily and anonymously participated in this study. The respondents, aged between 20 and 58 years (Mage = 40.10, SD = 6.38), constituted a single study group with intra-group variables. Participants completed "The Ruminative Responses Scale" (Nolen-Hoeksema & Morrow, 1991; Marchetti et al., 2018), which consists of 22 items and assesses overall rumination as well as its subcomponents: brooding, reflection, and depression. Additionally, participants evaluated their confidence in the effectiveness of their responses and the perceived ease or difficulty of responding to specific questionnaire items, emphasizing the certainty of their assessments. The study also considered participants’ age characteristics and medical diagnoses when analysing rumination. To assess metacognitive beliefs related to rumination, thought control, and cognitive self-consciousness, the Metacognitions Questionnaire-30 (MCQ-30) (Wells & Cartwright- Hatton, 2004) was employed. Results. The findings revealed significant variability in levels of rumination, brooding, reflection, and depression among the participants. The majority of respondents exhibited moderate levels of rumination, with brooding being more prevalent than reflection. Confidence in responses was found to be higher among individuals with lower levels of rumination and depression, whereas those with elevated brooding and reflection scores demonstrated greater confidence in their responses. Military personnel with documented medical diagnoses exhibited significantly higher levels of rumination and depression compared to their counterparts without such diagnoses, with particularly pronounced rates observed among individuals diagnosed with post-traumatic stress disorder (PTSD). Furthermore, worry was identified as a significant factor influencing all measured variables: participants with high levels of worry demonstrated increased levels of rumination, brooding, reflection, and depression, while those with lower worry levels displayed more balanced psychological indicators. Discussion and Conclusions. This study provides an in-depth analysis of rumination and its subcomponents – brooding, reflection, and depression – among Ukrainian military personnel. The findings contribute to a deeper understanding of the psychological mechanisms underlying mental health disorders in military populations, underscoring the importance of targeted psychotherapeutic interventions. Specifically, elevated levels of rumination may be associated with an increased risk of developing mental health conditions such as PTSD and anxiety disorders. These results highlight the necessity of incorporating ruminative thinking patterns into psychological rehabilitation programs for military personnel. Future research should focus on the development of interventions aimed at modifying maladaptive ruminative thinking and evaluating their effectiveness within psychotherapeutic frameworks. Additionally, investigating individual and situational factors that may contribute to the reduction of ruminative thinking in military personnel represents a critical avenue for further exploration.